1978
DOI: 10.1210/jcem-46-4-649
|View full text |Cite
|
Sign up to set email alerts
|

Somatomedin Bioactivity in Serum and Amniotic Fluid during Pregnancy*

Abstract: Somatomedin bioactivity (SMA) in maternal serum, as measured by hypophysectomized rat cartilage assays, was low during early and late pregnancy but was similar to normal nonpregnant control levels near 28 weeks and at term pregnancy. At term, the mean level of SMA in cord serum was significantly less than in maternal serum, and greater than in amniotic fluid. The mean level of SMA in amniotic fluid was higher at term than in early pregnancy. No significant correlation was noted between SMA levels in amniotic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…The purified SM revealed a single protein band on sodium dodecyl sulfate polyacrylamide gel electrophoresis, and the preliminary amino acid sequence determination indicated that this purified SM was more than 75% pure. imately 4000 U/mg, as measured by a hypophysectomized rat cartilage bioassay (14), where 1 U SM activity was equivalent to the SM activity present in 1 ml pooled serum obtained from normal adult male volunteers. The molecular weight was approximately 7500, as determined by gel filtration, sodium dodecyl sulfate polyacrylamide electrophoresis, and amino acid analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The purified SM revealed a single protein band on sodium dodecyl sulfate polyacrylamide gel electrophoresis, and the preliminary amino acid sequence determination indicated that this purified SM was more than 75% pure. imately 4000 U/mg, as measured by a hypophysectomized rat cartilage bioassay (14), where 1 U SM activity was equivalent to the SM activity present in 1 ml pooled serum obtained from normal adult male volunteers. The molecular weight was approximately 7500, as determined by gel filtration, sodium dodecyl sulfate polyacrylamide electrophoresis, and amino acid analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reports have shown the presence of bioreactive SLA in human amniotic fluid, but at much lower concentrations than those found in plasma (Bala and Smith, 1976;Bala et al, 1978). Immunoactive SLA, however, has been reported to be present in amniotic fluid at both higher (Moberg et al, 1976) and lower (Frankliri et al, 1979) reflect the different sensitivities and cross-reactivities of the assays to the various somatomedins.…”
Section: Discussionmentioning
confidence: 95%
“…In human amniotic fiuid bioreactive SLA has been reported to increase from very low concentrations, relative to serum, at 16-20 weeks to higher, but still very low, concentrations at term (Bala et al, 1978). Concentrations of immunoreactive somatomedin-C decrease during this time (Chochinov et al, 1976).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The fetal fluids represent an additional source of nutrients and hormones for the fetus, including IGF-I and IGFBP-1 [23,24]. The mechanisms of control of utilization of amniotic hormones and nutrients are not understood.…”
Section: Amniotic Growth Factorsmentioning
confidence: 99%